Фантасмагория, или Сказки третьего тысячелетия: повести / Александр Романов - Романов Александр Анатольевич (Луч, 2011)
Экземпляры: ЦБ (20120627) / Инвентарный номер: 44011 / Цена: 230.08 / Авт.знак: Р 69 / ББК: 84(2Рос=Рус)6